(untitled) (Singaporean Journal of Business Economics and Management, 2016)
This study is an evaluation of organisational structure on management effectiveness with reference to Dangote Cement PLC in Gboko, Benue State. The specific objectives were to identify the type(s) of organisational structure adopted in Dangote Cement PLC, Gboko Plant, and its effect on management effectiveness, among others. The research adopted survey research design, the population consist of management personnel of the organisation, which was one hundred and fifty one (151). Purposive and simple random sampling techniques, primary and secondary data was used. Using Taro Yamane’s formula, the sample size of the study was used deduce to be one hundred and ten (110), while one hundred (100) questionnaire was well field and return, which formed the basis for the data analysis. Descriptive statistic, Pearson Product Moment Correlation, and Logistic Regression Analysis was used to analyse the objectives. The major findings revealed that; line and staff organisational structure and product/market organisational Structure are organisational structure adopted in the organisation, the correlation analysis result indicated that at P > 0.05 level of significance, organisational structure has a strong positive effect on managerial effectiveness with correlation coefficient of (r = 0.811) The Logistic Regression result revealed that; Centralisation (sig <= 0.05) w = 2.764 ) Formalisation (sig <= 0.01) w = 11.609 ) and effective Organisation Communication ( sig <= 0.01 ; w = 5.342 ) are structural variables that are significantly related with the effectiveness of managers in Dangote Cement PLC, Gboko Plant. The researcher concluded that effective organisational structure is sine qua non to management effectiveness and organisational performance, and recommends that organisation structure should be effectively designed for it provides the framework for the activities of the organisation, and its competitive ability.